Gastroenteric neuroendocrine neoplasms classification: Comparison of prognostic models. Issue 1 (28th June 2012) - Dolcetta‐Capuzzo, Anna; Villa, Valentina; Albarello, Luca; Franchi, Giulia M.; Gemma, Marco; Scavini, Marina; Di Palo, Saverio; Orsenigo, Elena; Bosi, Emanuele; Doglioni, Claudio; Manzoni, Marco F.
Abstract BACKGROUND: Gastroenteric neuroendocrine neoplasms (GE‐NENs) display highly variable clinical behavior. In an attempt to assess a better prognostic description, in 2010, the World Health Organization (WHO) updated its previous classification, and the European Neuroendocrine Tumors Society (ENETS) proposed a new grading and TNM‐based staging system. In the current study, the authors evaluated the prognostic significance of these models and compared their efficacy in describing patients' long‐term survival to assess the best prognostic model currently available for clinicians. METHODS: The study cohort was composed of 145 patients with extrapancreatic GE‐NEN who were observed from 1986 to 2008 at a single center and were classified according to the WHO and ENETS classifications. Survival evaluations were performed using Kaplan‐Meyer analyses on 131 patients. Only deaths from neoplasia were considered. A P value < .05 was considered significant. Prognostic efficacy was assessed by determining the Harrell concordance index (c‐index). RESULTS: Both the 2010 WHO and the ENETS classification were able to efficiently divide patients into classes with different prognoses. According to the model comparison, the ENETS TNM‐based staging system appeared to be the strongest. All combined models were effective prognostic predictors, but the model that included the 2010 WHO classification plus ENETS staging had a higher c‐index. CONCLUSIONS: Both the 2010 WHO classification and the ENETS staging system are valid instruments for GE‐NENs prognostic assessment, with TNM‐based stage appearing to be the best available choice for clinicians, both alone and in association with other classifications. Cancer 2013. © 2012 American Cancer Society.